The Use of Artificial Intelligence in Islamic Studies: An Analysis of Students’ Perceptions and the Need for Guidance Based on Islamic Values - Che Nordin, Mohd Khairul Naim; Othman, Nurin Aina; Mohd Azhar, Muhammad Hazim; Syed Abdul Rahman, Syed Mohammad Hilmi; Mohd Azhar, Abdul Hannan (Jurnal Usuluddin, 2025)
Artificial Intelligence (AI) represents an advanced technology capable of performing cognitive functions such as learning, problem-solving, and decision-making. Its integration into education, particularly through chatbots and natural language processing (NLP) technologies, has opened new avenues for more rapid and interactive learning processes. Nevertheless, concerns arise regarding the appropriateness of AI within Islamic Studies, a field that places great emphasis on the authenticity of knowledge and the continuity of scholarly transmission (sanad). Overreliance on generative AI without critical verification poses potential risks to the integrity of Islamic knowledge. This article aims to assess the perceptions and extent of AI usage among students specializing in Islamic Studies. A mixed-methods approach was employed, involving online surveys and semi-structured interviews. The findings reveal that most students actively use AI tools, particularly ChatGPT (58.64%), to support their learning activities. While respondents generally expressed positive perceptions towards AI, they also stressed the necessity for ethical guidelines and the incorporation of Islamic moral values in its use. In conclusion, AI holds significant potential as a supportive tool in Islamic Studies education. However, its application must be guided by ethical frameworks and aligned with the epistemological principles of Islamic scholarship. Such guidelines are essential to ensure that technology is utilized responsibly, without compromising the authenticity of knowledge transmission and the preservation of Islamic ethical values.